Efektifitas Pembelajaran Model Contextual Teaching dan Sains Teknologi Masyarakat terhadap Hasil Belajar Mahasiswa - Ikawati, Hastuti Diah; Anwar, Zul; Safitri, Nila Egidia (JOEAI (Journal of Education and Instruction), 2018)
This study aims to determine the effectiveness of contextual teaching learning models and community technology science models on student learning outcomes in the diffusion courses of educational innovation. This study uses quasi-experimental by collecting data using tests, documentation, interviews and observations. The results showed that the average value of student learning outcomes used in the learning model of community technology science was higher than the value of student learning outcomes used in the contextual teaching learning model. This is because the community's science technology model helps students better understand material related to problems found in real life so students become active in the learning process. In conclusion, the Contextual Teaching and Science learning model of community technology is more effective in improving student learning outcomes in the diffusion of education innovation courses. Keywords: Learning Outcomes, Contextual Teaching Learning Model, Science Technology Society.